Antioxidant Activity Aktivitas Antioksidan Ekstrak Etanol Daun Lerak (Sapindus rarak DC) Dengan Metode Peredaman Radikal Bebas DPPH - Asri, Fitriani; Suhaenah, Asriani; Maryam, St. (Makassar Pharmaceutical Science Journal (MPSJ), 2024)
FITRIANI ASRI. Antioxidant Activity Of Ethanol Extract Of Lerak eaves (Sapindus rarak) Using The DPPH Free Radical Reduction Method (Supervised by Asriani Suhaenah dan St. Maryam) Lerak leaves (Sapindus rarak) are a traditional plant used by the community to treat various diseases. The secondary metabolic compounds contained in the lerak plant (Sapindus rarak) which have potential as antioxidants are flavonoids, alkaloids, saponins, tannins, quinones, steroids and triterpenoids which are obtained through extraction using ethanol solvent. This research aims to determine the antioxidant activity of the ethanol extract of lerak leaves (Sapindus rarak) using the DPPH free radical reduction method (1,1-diphenyl-2-picrihydrazyl). The antioxidant value was measured using UV-Vis spectrophotometry at a wavelength of 516 nm. The calculation results show an IC50 value of 876,592 μg/mL (very weak category) while quercetin as a comparison has very strong antioxidant activity with an IC50 value of 1,882 μg/mL.